2014
DOI: 10.1007/s00429-014-0845-2
|View full text |Cite
|
Sign up to set email alerts
|

Working memory training impacts the mean diffusivity in the dopaminergic system

Abstract: Dopaminergic transmission plays a critical role in working memory (WM). Mean diffusivity (MD) is a sensitive and unique neuroimaging tool for detecting microstructural differences particularly in the areas of the dopaminergic system. Despite previous investigation of the effects of WM training (WMT) on dopamine receptor binding potentials, the effects of WMT on MD remain unknown. In this study, we investigated these effects in young adult subjects who either underwent WMT or received no intervention for 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 59 publications
(95 reference statements)
2
41
0
Order By: Relevance
“…Attention training drills are grounded in the emerging literature supporting experience-dependent plasticity [16][17][18][19] and are mostly based on the adult brain injury rehabilitation literature that has produced practice guidelines supporting this intervention. 20,21 A critical issue with this intervention approach is equivocal evidence for generalization or "transfer" of gains from cognitive training to nontrained tasks, including everyday, "real-world" activities, in pediatric brain injury or other childhood conditions.…”
Section: The Treatment Evidence In Acquired Pediatric Brain Injurymentioning
confidence: 99%
“…Attention training drills are grounded in the emerging literature supporting experience-dependent plasticity [16][17][18][19] and are mostly based on the adult brain injury rehabilitation literature that has produced practice guidelines supporting this intervention. 20,21 A critical issue with this intervention approach is equivocal evidence for generalization or "transfer" of gains from cognitive training to nontrained tasks, including everyday, "real-world" activities, in pediatric brain injury or other childhood conditions.…”
Section: The Treatment Evidence In Acquired Pediatric Brain Injurymentioning
confidence: 99%
“…10, 11 Changes in MD have been shown to be uniquely sensitive to neural plasticity. 11, 12 In particular, MD in the dopaminergic system has been shown to be quite sensitive to pathological, pharmacological and cognitive differences or changes related to dopamine. 12, 13, 14, 15 On the other hand, FA is known to be relatively more strongly associated with microstructural properties related to brain connectivity and sensitive to increases in axonal membrane thickness, diameter and/or the amount of parallel organization of the axons and can also reflect the process of neural plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MDDS has been shown to be more sensitive to detect the pathology of the dopaminergic system (Parkinson's disease) than other magnetic resonance imaging (MRI) measures and positron emission tomography (PET) (Péran et al 2010;Seppi et al 2004). In addition, MD and MDDS have been shown to be sensitive to detect the neural plasticity, including very rapid changes (Razek et al 2011;Sagi et al 2012;Takeuchi et al 2014b). For example, Takeuchi et al (2014b) showed working memory training of 4 weeks lead to changes in MDDS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MD and MDDS have been shown to be sensitive to detect the neural plasticity, including very rapid changes (Razek et al 2011;Sagi et al 2012;Takeuchi et al 2014b). For example, Takeuchi et al (2014b) showed working memory training of 4 weeks lead to changes in MDDS. In addition, in a study by Sagi et al (2012), subjects underwent two series of scans approximately 2 h apart.…”
Section: Introductionmentioning
confidence: 99%